On the effect of trailing edge under-filing on the apparent slip factor of centrifugal impellers - Litfin, Oliver; Delgado, Antonio (ASME-JSME-KSME 2019 8th Joint Fluids Engineering Conference, AJKFluids 2019, 2019)
The trailing edge flow in a centrifugal impeller is of great importance as it determines the exit flow velocity triangle and therefore the work transferred to the fluid. The present study deals with the impact of trailing edge under-filing on the impeller exit flow and the resulting slip factor. Different under-filed trailing edge shapes are investigated by means of numerical simulations. 2D-RANS simulations are performed for a wide range of blade angles. For the default cut-off trailing edge configuration an attached and a separated flow regime around the blade trailing edge can be distinguished, mainly depending on the blade exit angle. The occurrence of the separated flow regime is associated with a significant change in performance, mainly due to the reduced flow deflection at the impeller exit. Under-filing of the trailing edge leads to less apparent slip for blade angles up to 40 degrees. This can be attributed to the fact that under-filing prevents the attached flow regime occurring in case of the default trailing edge. Additional DES simulations provide deeper insight into the detailed flow structures involved in this phenomena and reveal the turbulent flow structures in the trailing edge and wake flow. The obtained results provide a deep insight into trailing edge flows in centrifugal pump impellers and help to get a better understanding of the phenomena involved. Moreover, the results can provide an explanation to the often observed deviation of the apparent impeller slip from the theoretical slip predicted by slip factor models.
CRIS-Team Scopus Importer:2019-12-31